Voices on Instagram Usage in English Language Teaching: A Systematic Review - Pasha, Nariza Ayu; Pratolo, Bambang Widi; Inawati, Iin (Ahmad Dahlan Journal of English Studies, 2023)
In this digital era, Instagram is growing rapidly not only as social media but also as an educational platform, especially in English language teaching and learning. Research investigating further Instagram usage in English language teaching and learning through the systematic review is still scarcely reported. The purpose of this study is to investigate and synthesize the contribution of previous research (2017-2022) related to Instagram usage and its advantages in the ELT context. Several studies were found on the Sinta, ERIC, and Google Scholar databases. 25 articles were selected based on specified criteria stages that refer to Preferred Reporting Items for Systematic Review and three stages of Meta-Analyses (PRISMA). The findings of this research showed the four main themes examined in Instagram in ELT context, namely students' perceptions of using Instagram in learning English (40%), the topic of improving students' English skills using Instagram (32%), exploring English learning activities through Instagram (20%), and Instagram use in English teaching and learning as perceived by teachers (8%); and the five main advantages of using Instagram for learning English: improving language skills (40%), providing fun learning to students (23%), fostering creativity, motivation, and self-confidence (19%), increasing student understanding in ESP classes (9%), and provide opportunities for collaboration (9%).